Composition, distribution, and abundance of macrobenthos in seagrass beds of Carles, Iloilo, Philippines - Pamonag, Kaola Alezandra T. (2016.)
Seagrass beds in Carles, Iloilo were sampled to determine macrobenthic composition, density and distribution as well as community indices. Sampling was done by setting a 50-meter transect in three stations within Carles and randomly collecting sediment samples form three sampling points within each transect by using a NaGISA corer. The overall mean macrobenthic density was 1,100.33 ind.?m-2 composed of organisms belonging to 52 taxa, of which 40 were polychaete species which comprised the largest density (61.7%) among the 6 major group present, namely, crustaceans (21.1%), oligochaetes (13.7%), nematodes (2.3%), nemerteans (0.6%), and turbellarians (0.6%). Among the polychaete families, Family Syllidae (29%), Nereidae (14%), Sabellidae (9%), Spionidae (9%), and Capitellidae (7%) were the most abundant. One-way ANOVA showed that densities were significantly different (F= 24.859, p=0.001) among stations. Highest macrobenthic density was in Station 3 (2,508.75 ind.?m-2) followed by Station 1 (641.33 ind.m-2) while it was lowest in Station 2 (150.90 ind. ind.?m-2). Density and diversity of macrobenthos were primarily influenced by silt and clay content (%), dissolved oxygen concentrations, turbidity, seagrass biomass and seagrass cover (R= 0.778) for seagrass provide protection form predators, stabilize sediments and increase food availability. Percent silt and clay content (R= 0.708) and median grain size (R=0.693) showed strong positive relationships with macrofaunal density, which provided optimum habitat conditions for polychaete species particularly interstitial syllids Exogone sp. and other deposit feeding macrobenthos. Species richness and diversity showed a direct linear trend with mean macrobenthic densities but species evenness was constant throughout all stations which signify equally distributed macrobenthic species populations among seagrass stations.
Special Problem (Undergraduate, Bachelor of Science in Biology) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo
Keywords: Seagrass; Macrobenthos -- Carles; Polychaete; Exogone sp